2017
DOI: 10.4274/tjps.44127
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Profiles and Genotypes of <i>Acinetobacter baumannii</i> Isolates and <i>In Vitro</i> Interactions of Various Antibiotics in Combination with Tigecycline and Colistin

Abstract: ÖZAmaç: Bu çalışmada nozokomiyal çoklu ilaç dirençli (ÇİD) Acinetobacter baumannii izolatlarının antibiyotik direnç profilinin belirlenmesi, moleküler düzeyde tiplendirmelerinin yapılması ve dirençli izolatlarda antibiyotik kombinasyonlarının aktivitesinin araştırılması amaçlandı. Gereç ve Yöntemler: Seksen dört ÇİD A. baumannii izolatına karşı tigesiklin (TGC), kolistin (CL), amikasin (AK), siprofloksasin (CIP), meropenem (MR), moksifloksasin (MXF) ve rifampisinin (RF) minimum inhibitör konsantrasyon (MİK) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Thirteen studies with 189 isolates tested meropenem–colistin combination therapies and showed a pooled synergy rate of 58.8% (95% CI, 29.4%–85.6%) and a heterogeneity ( I 2 ) of 92.3% ( Figure 7 ); thus, the random-effect model was applied in the meta-analysis. 7 , 11 , 29 , 36 , 40 , 41 , 43 , 44 , 47 , 49 , 54 , 56 , 62 Two isolates were found to be antagonistic. There are six studies that include meropenem-susceptible strains; however, no detailed number of isolates was found in some of these studies, which resulted in the unavailability of subgroup analysis.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Thirteen studies with 189 isolates tested meropenem–colistin combination therapies and showed a pooled synergy rate of 58.8% (95% CI, 29.4%–85.6%) and a heterogeneity ( I 2 ) of 92.3% ( Figure 7 ); thus, the random-effect model was applied in the meta-analysis. 7 , 11 , 29 , 36 , 40 , 41 , 43 , 44 , 47 , 49 , 54 , 56 , 62 Two isolates were found to be antagonistic. There are six studies that include meropenem-susceptible strains; however, no detailed number of isolates was found in some of these studies, which resulted in the unavailability of subgroup analysis.…”
Section: Resultsmentioning
confidence: 98%
“…For meropenem–colistin combinations ( Figure 4 ), tests conducted on 132 isolates in 12 studies yielded a synergy rate of 60.4% (95% CI, 24.7%–91.8%), and no isolate was antagonistic. 7 , 14 , 15 , 21 , 23 , 44 , 47 , 53 , 54 , 56 , 61 , 62 Heterogeneity ( I 2 ) was calculated to be 89.8%, and thus, the random-effect model was applied in the meta-analysis. There are five studies on meropenem-susceptible strains; however, no detailed information on the number of isolates was found in some of these studies, which resulted in the absence of subgroup analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(28) (12,14,27,29) . Seftazidime ise A. baumannii suşlarında %11-22, P. aeruginosa suşlarında %70-85 oranlarında duyarlılık olduğu görülmüştür (12,14,27,29) (3,14,(19)(20)(21)27,30) . Pseudomonas suşlarında ise tobramisine %70-89, amikasine %62-88, gentamisine %66-77 oranlarında duyarlılık olduğu görülmüştür (15,27,(30)(31)(32) .…”
Section: Pseudomonas Aeruginosa N = 77unclassified